2019
DOI: 10.3390/vaccines7010017
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Immune Memory after a Pneumococcal Polysaccharide Vaccine Booster in a High-Risk Population Primed with 10-Valent or 13-Valent Pneumococcal Conjugate Vaccine: A Randomized Controlled Trial in Papua New Guinean Children

Abstract: We investigated the immunogenicity, seroprotection rates and persistence of immune memory in young children at high risk of pneumococcal disease in Papua New Guinea (PNG). Children were primed with 10-valent (PCV10) or 13-valent pneumococcal conjugate vaccines (PCV13) at 1, 2 and 3 months of age and randomized at 9 months to receive PPV (PCV10/PPV-vaccinated, n = 51; PCV13/PPV-vaccinated, n = 52) or no PPV (PCV10/PPV-naive, n = 57; PCV13/PPV-naive, n = 48). All children received a micro-dose of PPV at 23 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…A study of PCV immunogenicity in Papua New Guinea assessed the immunogenicity and persistence of immunity against pneumococcus induced by two different vaccination schedules in native children. They found that priming with either a 10-valent or a 13-valent PCV at one, two and three months of age, followed by a booster dose of the 23-valent polysaccharide vaccine (PPV23) at nine months of age resulted in protective immune responses in children challenged at 23 months of age [1]. This is an important finding in this setting, where strong immunological priming and broad serotype coverage are needed to protect children at high risk of disease.…”
mentioning
confidence: 99%
“…A study of PCV immunogenicity in Papua New Guinea assessed the immunogenicity and persistence of immunity against pneumococcus induced by two different vaccination schedules in native children. They found that priming with either a 10-valent or a 13-valent PCV at one, two and three months of age, followed by a booster dose of the 23-valent polysaccharide vaccine (PPV23) at nine months of age resulted in protective immune responses in children challenged at 23 months of age [1]. This is an important finding in this setting, where strong immunological priming and broad serotype coverage are needed to protect children at high risk of disease.…”
mentioning
confidence: 99%
“…1 ), of which 47 studies (78 publication reports) satisfied our eligibility criteria. 10 , 11 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ,…”
Section: Resultsunclassified
“… 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 93 , 94 , 95 , 96 The remaining 28 studies (54 publication records) from 2009 to 2023 were included in the network meta-analyses. 10 , 11 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , <...…”
Section: Resultsmentioning
confidence: 99%
“…Until new PCVs including more serotypes than the current 10- and 13-valent vaccines or serotype-independent vaccines become available, 23vPPV booster vaccination could provide these high-risk children with broader protection than induced by current PCVs alone. We have previously shown that PPV induces serotype-specific systemic IgG responses in PNG infants vaccinated with PCV as well as non-PCV recipients, with no evidence of inducing hypo-responsiveness [3] , [39] , [40] . We here show that a PPV booster results in enhanced mucosal IgA and IgG responses in PCV-primed PNG infants, which importantly could protect children against serotype-specific acquisition and carriage.…”
Section: Discussionmentioning
confidence: 95%